Theranostics: A treasured tailor for tomorrow - S Jeelani; R C Jagat Reddy; Thangadurai Maheswaran; G S Asokan; A Dany; B Anand (Wolters Kluwer Medknow Publications, 2014)
Emerging as a targeted, safe, and efficient pharmacotherapy is the approach of theranostics, which focuses on patient-centered care. It is a combination of diagnosis and therapeutics. It provides a transition from conventional medicine to personalized medicine. It deals with the custom made treatment plan based on uniqueness of every individual thus resulting in right drug for the right patient at the right time. Genetics plays a significant role in theranostics. Theranostics provides a cost-effective specific successful treatment protocol. Pharmacogenetics, proteomics and biomarker profiling forms the backbone of theranostics. The role of theranostics is interestingly appreciated at multi levels with special consideration in oncology wherein nano formulations in the form of liposomes, dendrimers, polymeric nanoparticles, metallic nanoparticles, quantum dots and carbon nanotubes play a very important role. Thus, theranostics is a holistic transition from trial and error medicine to predictive, preventive and personalized medicine leading to improved quality care of pharmacotherapy.